Isochronous Wireless Network for Real-time Communication in Industrial Automation - Trsek, Henning (Technologien für die intelligente Automation, Technologies for Intelligent Automation, 2016)
This dissertation proposes and investigates an isochronous wireless network for industrial control applications with guaranteed latencies and jitter. Based on a requirements analysis of real industrial applications and the characterisation of the wireless channel, the solution approach is developed. It consists of a TDMA-based medium access control, a dynamic resource allocation and the provision of a global time base for the wired and the wireless network. Due to the global time base, the solution approach allows a seamless and synchronous integration into existing wired Real-time Ethernet systems.